Study of Leadership Ability Based on Emotional Competence: a Case Study of Teamwork Performance in Indonesia - Agustinus Wardi; Lilik Kustiani; Bambang Supriadi (Global Management: International Journal of Management Science and Entrepreneurship, 2024)
With the concept of a Leadership Capability model based on the development of Emotional Competency which aims to anticipate the combination of Human Resource Management Strategy and team performance. As a statistical test, this research raises four variables, namely: Human Resource Management Strategy, Emotional Competency Based Leadership Ability, Job Crafting Behavior and Teamwork Performance. Empirical testing through a survey of 120 respondents, namely the school principal's work team consisting of the principal, deputy principal and head of administration who are members of the State High School development team in Central Java, Indonesia. Revealed the role of Leadership Ability based on Emotional Competence. In this research, to mediate Strategic Human Resource Management with team work performance. There are two limitations, the first is that the survey was only conducted at State High Schools and SKM in the province of Central Java, Indonesia, the second limitation is that it focuses on the mediator of Leadership Ability Based on Emotional Competence. This does not consider the existence of other variables from human resource management theory. intelligence theory, social exchange, service dominant logic, agency and others. At a practical level, the perspective of the relationship between Emotional Competency Based Leadership Capabilities, Strategic Human Resource Management and Teamwork Performance provides guidance on how public organizations such as schools can strive for value alignment to encouraging Emotional Competency Based Leadership Capabilities which in turn will improve team work performance